Transformational Leadership, HRM Competence, Information Technology, and the Performance of Public Service Employee - Suriyanti, Suriyanti (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2020)
This study aims to analyze the effect of Transformational Leadership, human resource management competency, and Information Technology on employee performance, and information technology mediates the relationship between Transformational Leadership, human resource management competency on the employee performance. The study used data obtained from the purposive sampling of the employee in the south Sulawesi provincial education office (N=88). The result of this study showed that transformational leadership, HRM competence, and information technology, both direct and indirect have a significant effect on the performance of the South Sulawesi Provincial Education Office.